Dynamics of Value Incongruence in Market Orientation and Turnover Intention in the Fixed Line Telecommunication Industry of Sri Lanka - Perera, Stanley; Wijetunga, Dinuka; Jayakody, J.A.S.K. (My University, 2008)
While the relationships between market orientation and employee commitment have been discussed in marketing literature, relationships between value incongruence, employee commitment and employee turnover intention have been discussed in human resource literature. However, there are no studies that link market orientation to employee turnover; nor has value incongruence been discussed in marking literature. Some phenomena observed in a reputed telecommunication company in Sri Lanka, offered an empirical site to study the possibility of incorporating these concepts in a single model. It was found that value incongruence was formed by the gap between perceived company market orientation and market orientation of employees. Affective commitment emerged as a mediating variable between value incongruence and turnover intention. In addition, continuance commitment was found to moderate the relationship between affective commitment and turnover intention.